Aberrant DNA glycosylase-initiated repair pathway of free radicals in-duced DNA damage: implications for age-related diseases and natural aging - Matkarimov, B.T.; Saparbaev, M.K. (Вiopolymers and Cell, 2017)
Aerobic cellular respiration generates reactive oxygen species (ROS), which can damage macro-molecules including lipids, proteins and DNA. It was proposed that aging is a consequence of accumulation of naturally occurring unrepaired oxidative DNA damage. In human cells, approximately 2000 to 8000 DNA lesions occur per hour in each cell, i.e. 40000 to 200000 per cell per day. DNA repair systems are able to discriminate between regular and modified bases. For example, DNA glycosylases specifically recognize and excise damaged bases among vast majority of regular bases in the base excision repair (BER) pathway. However, mismatched pairs between two regular bases occur due to spontaneous conversion of 5-methylcytosine to thymine and DNA polymerase errors during replication. To counteract these mutagenic threats to genome stability, cells evolved special DNA repair systems that target the non-damaged DNA strand in a duplex to remove mismatched regular DNA bases. Base excision repair (BER) and mismatch repair (MMR) pathways initiated by mismatch-specific adenine- and thymine-DNA glycosylases (MutY/MUTYH and TDG/MBD4, respectively) can recognize and remove normal DNA bases in mismatched DNA duplexes. Under certain circumstances in DNA repair deficient cells bacterial MutY and human TDG can act in an aberrant manner: MutY and TDG remove Adenine and Thymine opposite to misincorporated 8-oxoguanine and damaged Adenine, respectively. These unusual activities lead either to mutations or futile DNA repair, thus indicating that the DNA repair pathways which target non-damaged DNA strand can act in an aberrant manner and introduce genome instability in the presence of unrepaired DNA lesions. Both accumulation of oxidative DNA damage in cells and the aberrant DNA repair can contribute to cancer, brain disorders and premature senescence.